P-194 Luminal Adenosine Production by Intestinal Epithelial Ecto-5'- nucleotidase (CD73) Is a Regulator of Intestinal Homeostasis and Infection by Salmonella Typhimurium. (1st March 2016) - Kao, Daniel; Saeedi, Bejan; Kitzenberg, David; Schwisow, Kayla; Colgan, Sean; Kominsky, Douglas
Abstract : Background: Intestinal dysbiosis is a hallmark of inflammatory bowel disease and has been implicated in its pathogenesis. Thus, characterization of host-microbe interactions at the intestinal mucosa is crucial for an understanding of the factors that shape the intestinal microbiota. Purine metabolism is a vital regulator of the virulence of enteric pathogens. Ecto-5'-nucleotidase (CD73) is expressed abundantly on the apical surface of intestinal epithelial cells (IEC) and is the terminal enzyme in the generation of extracellular adenosine (Ado). While it has been shown that Ado signaling in IEC results in a number of tissue protective effects during inflammation, a rationale for its apical expression has been lacking. We hypothesized that the highly polarized expression of CD73 is indicative of an important role for extracellular Ado as a mediator of host-microbe interactions. Methods: The effect of Ado and other purine metabolites on the growth of the enteric pathogen Salmonella typhimurium was examined in culture. CD73 expression was knocked down in cultured IEC using short hairpin RNA to examine the effects of extracellular Ado on Salmonella infection in vitro. A novel transgenic mouse was generated with IEC-specific knockout of CD73 (CD73 f/f x Villin-Cre) and used to examine how luminal Ado production in vivo affects enteric Salmonella infection. Results: Ado has a dose-dependent bacteriostatic activity against Salmonella in culture. This antimicrobial activity is not shared by the related purine metabolites 5'-adenosine monophosphate, inosine, or hypoxanthine. This antimicrobial activity is reflected in vivo in a Salmonella colitis model, where colonization of the cecum and colon by Salmonella increases 10-fold in the CD73 f/f x Villin-Cre mice, which are defective in luminal adenosine production. Interestingly, however, despite the higher luminal burden of Salmonella, CD73 f/f x Villin-Cre mice are protected against Salmonella colitis, as demonstrated by attenuated weight loss, decreased colon shortening, and less extraintestinal dissemination of Salmonella . These findings suggest that Ado is important for Salmonella virulence. Consistent with this hypothesis, knockdown of CD73 expression in cultured IEC results in dramatic defects in intraepithelial replication and transepithelial translocation by Salmonella . Finally, the effect of Ado is also seen in other pathogenic as well as commensal enteric bacteria. Conclusions: This study demonstrates a novel antimicrobial role for Ado in the gastrointestinal tract and supports a role for Ado as an innate immune mediator. Through this mechanism, CD73 expression may contribute to shaping the intestinal microbiota as a result of luminal Ado production. In addition, extracellular Ado is important in the induction of Salmonella virulence during enteric infection. These findings have broad implications for Ado as an important regulator of host-microbe interactions.